Serum albumin coated stellate mesoporous silica nanocomposites inhibit metastatic outgrowth in zebrafish embryos - Asokan, Nandini (2025)
Mesoporous silica-based nanoparticles (NPs) are promising tools for developing targeted therapeutic interventions in cancer. Endowed with a large pore silica shell suitable for drug encapsulation and with a responsive magnetic core, iron oxide stellate mesoporous silica (IO STMS) NPs stand out. Yet, their impact and potential toxicity on relevant in vivo models has not been carefully tested yet. Herein, we assessed the impact of these IO STMS nanocomposites in a syngeneic metastasis assay in zebrafish. NPs were surface-modified with human serum albumin (HSA) and loaded or not with the chemotherapeutic doxorubicin (DOX). In vitro, DOX-loaded NPs were expectedly more toxic to zebrafish melanoma (Zmel) cells than no-DOX NPs. In zebrafish embryos, the NPs were rapidly distributed through blood circulation and were found to colocalize over time with the vascular endothelium and local macrophages. Suprisingly, the NPs efficiently reduced the outgrowth of Zmel tumoral masses in an experimental metastasis assay in zebrafish embryos regardless of their loading with DOX. The anti-metastatic effect of these NPs was further improved by increasing the amount of HSA coating, also resulting in higher embryo survival. Altogether, IO STMS NPs showed promising cytotoxic effects on a relevant zebrafish metastasis model, inhibiting metastatic outgrowth in vivo independently of the drug loading. This opens the door to further testing for better exploiting their targeting and drug delivery potentialities.